Investigating the Potential of 3D Printed Violins in Instrumental Teaching and Learning Contexts: Perspectives from Luthiers, Musicians and Instrumental Teachers. - Dunne, Sarah Ellen (Trinity College Dublin. School of Education. Discipline of Education, 2025)
This research seeks to fuse two domains of practice: violin making and 3D printing. Although music performance has been one of three core strands of the post-primary music curriculum since the 19th century, musical instrument provision presents challenges for teachers (Conaghan, 2022). Recurring concerns include instrument access (Hallam & Rogers, 2016), instrument quality (Campbell, 2013), and sonic and material variations between brands that impede engagement and progression (Sturman, 2019). Distinctly, 3D scanning and printing tools for digital mapping and fabrication offer a model for democratising instrument access, redesigning structural quality, and standardising instrument sonics. Over three years, with the assistance of five luthiers, 10 professional musicians, and five instrumental music teachers, and under three headings of conservation and making, perceptions and value, and performance and musicking, this exploratory study aimed to accomplish the following goals: i. To map the technical specifications and material properties required to achieve comparable sound quality and durability between traditional and 3D printed violins. ii. To evaluate the perceptions and values of musicians and luthiers who use 3D printed instruments. iii. To synthesise how 3D printed violins affect opportunities for teachers in music performance. Data was generated from multiple sources using a mixed-methods research design and based on socio-cultural learning theories. Semi-structured interviews with instrumental teachers assessed user needs, as well as instrument scanning, modelling, and 3D printing, were conducted in Year One. Luthiers completed questionnaires, while professional musicians completed sound recordings and questionnaires in Year Two. Finally, interviews with instrumental music teachers took place in Year Three. The analyses comprised reading, coding, thematic classification, and triangulation. Three key findings emerged from the study. Firstly, although polymer-based materials cannot replicate the unique variations of traditional woods, filaments with strategic layering and infill patterns can be used to engineer the density and flexibility approximation needed to achieve comparable acoustic performance. This finding extends existing literature from Doddamani et al. (2023). Secondly, 3D printed instruments garnered mixed responses from musicians and luthiers. While some musicians appreciated their affordability, customisability, and preservation potential, others remain concerned about their sonic authenticity and durability. Meanwhile, luthiers expressed concerns about losing their traditional craftsmanship but acknowledged the instruments innovative potential for custom designs. This finding aligns with research conducted by Duerinck et al. (2020), which found that participants viewed 3D printed musical instruments as educational or experimental rather than professional performance tools. Thirdly, their potential integration into an educational context offers pedagogical advantages, such as cost-effectiveness and ease of repair. Teachers reported that the potential of 3D printed violins lies in aiding access to instruments, increasing provision, and fostering tangible links to STEAM (science, technology, engineering, arts, and mathematics, and their interconnectivity), which helps align this research with curriculum outcomes (Ulbrich et al., 2024). The results of this study have implications for the conservation, redesign, and fabrication of musical instruments, as well as for how instrumental teachers might diversify technologies in music education. 3D printing based on school needs offers a decentralised, individualised, and localised model of instrument acquisition. This study examines the conservation, adaptation, performance potential, and limitations of 3D printing in the context of music. In the process, it provides an alternative 3D printed violin model that builds on prior digital modelling research.
APPROVED
Keywords: 3D printed violins; Additive Manufacturing; Acoustic performance analysis; Material acoustics in instrument design; Music education technology